(3CHhGH ef GdfMhs - (3Ydj Hf eMeO GdgQhj GdfMhj, CHh GdMSf , J (B370 (3g` s; (3Ydj Hf eMeO GdgQhj GdfMhj, CHh GdMSf,J (B370 (3g` ? s
(3ChdgG (B:s
(3bGd GdEeGe CHhGdMSf SCdJfj CjOc Gddg Cf CLeY dc CHhGHkG ef GdfMh bO PcQfGgG eJaQbI aj cJGHfG GdedbH HGdPNGFQ s
(3BNQgG (B:s
(3hbGd BNQ(B: (3ef GddGA de jMLLf jHZjf MSHg hdcf djbJdf GdHQF GdeZadG Je GdcJGH CLeY hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3Hbde eged GdfbW ZGdHkGs
(3YdjgG ebGHdIs
(3HgG fXGe GdJYbjHIs
(3LeYgG GdeDda ef cJGHg GdedbH HGdPNGFQ hgh aj GdfMhs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdfMhs